2009
DOI: 10.1056/nejmoa0802289
|View full text |Cite
|
Sign up to set email alerts
|

Machine Perfusion or Cold Storage in Deceased-Donor Kidney Transplantation

Abstract: Hypothermic machine perfusion was associated with a reduced risk of delayed graft function and improved graft survival in the first year after transplantation. (Current Controlled Trials number, ISRCTN83876362.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
691
3
14

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 956 publications
(721 citation statements)
references
References 26 publications
13
691
3
14
Order By: Relevance
“…11 This pioneering study created the rationale to investigate strategies for organ preservation based on machine perfusion of kidney or liver grafts. 24,25 Furthermore, it allows study of the molecular mechanisms leading to increased endothelial sensitivity to injury in the absence of shear stress, with the aim of discovery druggable targets to prevent endothelial and tissue damage during organ procurement. For this purpose, we analyzed the effects of shear stress interruption and cold storage on the hepatic endothelial phenotype and function, and developed a pharmacological strategy to maintain endothelial health in the setting of organ transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…11 This pioneering study created the rationale to investigate strategies for organ preservation based on machine perfusion of kidney or liver grafts. 24,25 Furthermore, it allows study of the molecular mechanisms leading to increased endothelial sensitivity to injury in the absence of shear stress, with the aim of discovery druggable targets to prevent endothelial and tissue damage during organ procurement. For this purpose, we analyzed the effects of shear stress interruption and cold storage on the hepatic endothelial phenotype and function, and developed a pharmacological strategy to maintain endothelial health in the setting of organ transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Moers et al have shown better 1 year graft survival and lower delayed graft function rates after machine perfusion MP in a cohort composing both DCD (n=42) and DBD kidneys (n=294) [12] and these findings were replicated in other studies [13,14]. However, Moers have stated later on that three years after transplantation machine perfusion MP had no advantage over cold storage in terms of graft survival in DCD kidney transplantation.…”
Section: Discussionmentioning
confidence: 87%
“…We assessed the effect of perfusion duration on the association between post pi-GST and DGF via stratified analysis with three duration categories (<8, [8][9][10][11][12][13][14][15][16], and >16 hours). The RR estimate for DGF with each unit increase in Log e (post pi-GST) were comparable for each category in the range of 1.3 to 1.6.…”
Section: Associations Of Perfusate Gst Pump Parameters and The Outcomentioning
confidence: 99%